Rocking chair defect generation in nanowire growth - Picraux, S. T. (2013)
We report the observation of a different defect generation phenomenon in layer-by-layer crystal growth. Steps at a nanowire liquid-solid growth interface, resulting from edge nucleated defects, are found to cause a gradual multiplication of stacking faults in the regions bounded by two edge defects. In the presence of a twin boundary, these generated defects continue to propagate along the entire nanowire length. This rocking chair generation mechanism is a unique feature of nanoscale layer-by-layer growth and is significantly different from well-known defect multiplication mechanisms in bulk materials.